EXAMINING THE IMPACT OF GAME-BASED FORMATIVE ASSESSMENT ON STUDENTS’ UNDERSTANDING AND PARTICIPATION IN A HUMAN-COMPUTER INTERACTION COURSE (Practitioner Research, 2021)
This study discusses an attempt to examine the impact of gamebased formative assessment on the students’ knowledge in a Human-Computer Interaction (HCI) course, which is a fundamental subjectfor Multimedia students. This course is important to expose them to the ideas of user interface and interaction design methodologies, skills, and values that are required for them to develop a practicalinteraction design system. The respondents in this research were 63 undergraduates who enrolled in an HCI course in a public university in Malaysia. An experimental research design was employed wherebythe respondents were conveniently assigned to two groups; control (33) and experimental (30). Eight paper-based formative assessments were given to the control group, while eight online game-based evaluations were given to the experimental group. The students’ scores are recorded to assess their understanding of the learning content and their participation in the HCI classroom. A test was also administered at the end of the semester and utilised as a data collection tool to examine the effectiveness of the intervention in terms of student comprehension. The information was then gathered and analysed using descriptive and ANOVA statistical methods. The students’ involvement was reflected through an opinion survey that was given to the students at the end of the semester. The findings revealed that students who participated in a game-based formative assessment shown greater understanding and involvement than students who participated in a formative paperbased evaluation, implying that introducing a scope of game-based formative assessments improved the understanding and participation in the HCI course classroom.